Synthesis in vitro of the full-length complement of defective-interfering particle RNA of vesicular stomatitis virus. - Chanda, P K (1980)
Under appropriate reaction conditions in vitro, four different defective-interfering particles of vesicular stomatitis virus have been shown to synthesize the full-length complement of their RNAs. The reaction involved preinitiation of the core particles with ATP and CTP, followed by RNA chain elongation in the presence of the beta, gamma-imido analogue of ATP, AdoPP[NH]P, and the three normal ribonucleoside triphosphates. By hybridization of the in vitro synthesized plus strand with the standard genome RNA followed by RNase treatment of the heteroduplexes, we have shown that the RNA of a defective-interfering particle derived from the 3' end of the genome RNA has evolved by an internal deletion of the standard genome.